EFFECTIVENESS OF THE LAMPUNG CIVIL SERVICE POLICE UNIT'S AUTHORITY: AN EDWARDS III AND SWOT-TOWS ANALYSIS - Muhamad Iwan; M. Yusuf S. Barusman (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes the effectiveness of the implementation of authority by the Lampung Province Civil Service Police Unit (Satpol PP) in enforcing public order and community tranquility (Trantibum), using Edwards III's four-variable framework (communication, resources, disposition, and bureaucratic structure), enriched by Ansell and Gash's collaborative governance perspective. Employing a qualitative case study approach, data were collected through in-depth interviews with twelve informants across organizational levels, participant observation of three field operations, and a document review of the 2024 Minimum Service Standards (SPM) Evaluation Report for Trantibum. The findings show that the authority of the provincial Satpol PP is coordinative rather than command-based, and its effectiveness is constrained by statutory ambiguity surrounding the concept of 'facilitation' and by systemic resource deficits. Relational analysis reveals that the four Edwards III variables do not operate independently; rather, they form a pattern of institutional mismatch: resource constraints weaken the effectiveness of policy communication, while dysfunction in the bureaucratic structure contributes to variations in implementers' dispositions in the field. A SWOT-TOWS analysis, validated through member checking, produced eight strengthening strategies fully accepted by key informants, with the formalization of coordination mechanisms and the clarification of facilitation criteria identified as short-term priorities. This study extends the Edwards III framework to coordinative intergovernmental relations and proposes the concept of adaptive facilitation as an institutional response to regulatory ambiguity.